Deciphering the robustness of pyrazolo-pyridine carboxylate core structure-based compounds for inhibiting α-synuclein in transgenic C. elegans model of Synucleinopathy. Issue 17 (1st September 2020) - Maqbool, Mudasir; Rajvansh, Roshani; Srividya, Kottapalli; Hoda, Nasimul
Graphical abstract: Highlights: A series of pyrazolo-pyridine carboxylate hybrids (7a–7m) was designed and synthesized. Docking was used to understand the binding of the ligands with the protein. In vivo transgenic C. elegans model of Synucleinopathy was used to evaluate the ability of the test compounds to inhibit α-synuclein aggregation. Compounds 7b, 7g and 7i displayed 1.7, 2.4 and 1.5-fold inhibition of α-synuclein with respect to the control. Abstract: Parkinson's disease (PD), a calamitous neurodegenerative disorder with no cure till date, is closely allied with the misfolding and aggregation of α-Synuclein (α -Syn). Inhibition of α-Syn aggregation is one of the optimistic approaches for the treatment for PD. Here, we carried out hypothesis-driven studies towards synthesising a series of pyrazolo-pyridine carboxylate containing compounds (7a–7m) targeted at reducing deleterious α-Syn aggregation. The target compounds were synthesized through multi-step organic synthesis reactions. From docking studies, compounds 7b, 7g and 7i displayed better interaction with the key residues of α-Syn with values: −6.8, −8.9 and −7.2 Kcal/mol, respectively. In vivo transgenic C. elegans model of Synucleinopathy was used to evaluate the ability of the designed and synthesized compounds to inhibit α-Syn aggregation. These lead compounds 7b, 7g and 7i displayed 1.7, 2.4 and 1.5-fold inhibition of α-Syn with respect to the control. Further, the strategy of employing pyrazolo-pyridine-based compounds worked with success and these scaffolds could be further modified and validated for betterment of endpoints associated with PD.